(3aUhd CHbQGWs - (3CHbQGW GdMcjes
(3ChdgG (B:s
(3Efi CQi Gfg ef CaVd GdCehQ Cf jSJYed GdWHjH SGHb GdfXQ,bGd HbQGW hPdc Cfg EPG SHb aYde , hJbOe aCfPQ GdeQVi HGdTF GdMGVQ HeG jJe heVi s
(3BNQgG (B:s
(3CeG GdHRGb GdPi jNGdWg TF ef GdOe djS HGdcKjQ , hgh CMeQ fGUY aj hQe GdQFI agh aj Chd GdYdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQ Qbe (B63 (3ef agQS GdWH HYfhGf JbOeI GdeYQaI dCHbQGWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B168 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B248 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs